REMODELING OF THE RIGHT HEART AND THE LEVEL OF BRAIN NATRIURETIC PEPTIDE IN PATIENTS WITH CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION: A COMPARATIVE CROSS-SECTIONAL OBSERVATIONAL STUDY - A. A. Klimenko; N. A. Shostak; N. A. Demidova; I. V. Novikov; S. M. Sorokoletov; S. V. Madoyan (Рациональная фармакотерапия в кардиологии)
Aim. To study the right heart remodeling and level of N-terminal brain natriuretic peptide (Nt-proBNP) in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Material and methods. Patients (n=79) after pulmonary embolism were included into the study. The main group consisted of patients (n=43) with an increase in systolic pulmonary artery pressure (SPAP) >30 mm Hg: 30 (37.9%)  patients had pulmonary hypertension (PH) degree I, and 13 (16.5%)  — PH degree II–III. Group of comparison con- sisted of 36 patients expired pulmonary embolism and having SPAP <30 mm Hg. The control group consisted of 20 people. 6-minute walk test (6-MWT) and Doppler echocardiography were performed in all patients. Besides myocardial tissue Doppler echocardiography and assessment of Nt-proBNP level were performed in 38 and 71 patients, respectively. Results. Dyspnea occurred in 90.7% of patients with various degrees of PH and 80.5% of patients with normal SPAP. Patients without PH and with PH I complained of palpitations, weakness, fatigue, and dizziness with similar frequency. Patients with PH I were comparable with ones of comparison group in 6-MWT distance that dramatically decreased in patients with PH II–III. Enlargement of the right atrium (RA) and/or right ventricular (RV) was observed in 76.7% of patients with PH I and 100% of patients with PH II–III. RV diastolic function abnormalities (E/A<1 and E/A>2) were detected in 19.4%, 16.7% and 61.5% of patients of comparison group, PH I and PH II–III patients, respectively. According to myocardial tissue Doppler echocardiography Em/Am<1 was observed in 8 (72.7%) patients of the comparison group and in 13 (76.4%) patients with PH. Nt-proB-NP level was 17.3 [2.3, 33.9] fmol/ml in PH I patients and 142.1 [62.1, 171.8] fmol/ml in PH II–III patients. Nt-proBNP level was 6.5 [3.1, 18.3] fmol/mL in patients of the comparison group, and it was higher than this in patients of the control group (3.5 [1.8, 7.5 fmol/ml]. Conclusion. Various indicators of heart remodeling and RV diastolic dysfunction were found in the majority of patients after pulmonary embolism, including those with nor- mal SPAP. Elevation of Nt-proBNP level adequately reflects the severity of RV dysfunction in CTEPH patients only in PH II–III. This marker has low diagnostic value in patients with- out CTEPH and PH I patients.